In vitro antimicrobial activity of equine mesenchymal stromal cells and platelet lysate against common clinical pathogens - Avellar, Haileigh Kate (Kansas State University, 2021)
Septic arthritis is considered a medical emergency. Following bacterial colonization, significant morbidity and mortality can occur while requiring costly treatment. Antimicrobial properties of regenerative therapies including mesenchymal stromal cells and platelet products have been researched extensively in human medicine and have shown promising results. The purpose of this study was to evaluate bacterial suppression by equine platelet lysate (EPL) and adipose derived mesenchymal stromal cells (ASCs) in vitro. We hypothesized that both products would significantly inhibit the growth of Staphylococcus aureus (Sa) and Escherichia coli (Ec). Pooled blood from 10 horses was used for production of EPL. Mesenchymal stromal cells were isolated from adipose tissue harvested from the gluteal region of 3 horses. The study evaluated three treatment groups; 10X EPL, 1.6 million ASCs, and control using an incomplete unbalanced block design with repeated measurements. Optical density readings and colony forming units/ml were calculated at hours 0, 3, 6, 9, 12, 18, and 24. Decreased bacterial growth was seen at multiple time points for the Sa-ASC and Sa-EPL treatments supporting our hypothesis. Increased bacterial growth was noticed in the Ec-EPL group with no difference in the Ec-ASC treatment which did not support our hypothesis. A clear conclusion of the antimicrobial effects of EPL and ASCs cannot be made from this in vitro study. Although it appears ASCs have a significant effect on decreasing the growth of Sa, further studies are needed to explore these effects particularly in gram-positive bacteria.
Keywords: Platelet lysate; Mesenchymal stromal cell; Antimicrobial; Equine; MSC